Sejumlah Faktor yang Melandasi Persepsi dan Perilaku Dokter Hewan terhadap Resistansi Antimikrob dan Penggunaan Antimikrob - Sitanggang, Vera Paulina; Wicaksana, I Gede Hendra Prasetya; Besung, I Nengah Kerta; Mahatmi, Hapsari (Jurnal Veteriner; Vol 23 No 3 (2022)DO - 10.19087/jveteriner.2022.23.3.424, 2022)
Antimicrobial resistance (AMR) is the ability of bacteria to withstand the effects of drugs so that bacteria do not die after the administration of antimicrobials and the function of the drug does not work at all. This incident is caused by the uncontrolled use of antimicrobials which can cause a global crisis on human and animal health in the future. This study aims to determine the factors that influence the behavior and perceptions of veterinarians in the province of Bali on the use of antimicrobials and antimicrobial resistance. A total of 204 veterinarians were used as research samples through a survey using a Likert system and then the results of differences in veterinary responses to the frequency of prescribing were analyzed by Kruskal-Wallis. The results showed that antimicrobials were given to half of the patients treated weekly, and the factors that influenced the administration of antimicrobials were the history of antimicrobial use, level of safety, experience, potency, side effects, and the risk of increasing antimicrobial resistance. The cost of culture testing and the price of antimicrobials are the biggest barriers for small animal veterinarians but not for livestock veterinarians. All respondents acknowledged that most sources of information on AMR were easy to obtain and useful for them. The group of veterinarians who practice small animals and livestock practitioners agree that AMR is a serious common threat in the future. This study provides important insights into the application of veterinary medical procedures in the province of Bali and will later become a reference in increasing regulation control over the use of antimicrobials.